2021
DOI: 10.1007/s12571-021-01156-w
|View full text |Cite
|
Sign up to set email alerts
|

Cross-national analysis of food security drivers: comparing results based on the Food Insecurity Experience Scale and Global Food Security Index

Abstract: The second UN Sustainable Development Goal establishes food security as a priority for governments, multilateral organizations, and NGOs. These institutions track national-level food security performance with an array of metrics and weigh intervention options considering the leverage of many possible drivers. We studied the relationships between several candidate drivers and two response variables based on prominent measures of national food security: the 2019 Global Food Security Index (GFSI) and the Food Ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 50 publications
3
29
0
Order By: Relevance
“…Muhammad et al [ 160 ] found that the purchase of pricier fruits and milk was particularly sensitive to changes in income and prices. According to Allee et al [ 161 ], an increase in income directly influences an improvement in the food security status of the population, but the strength of this effect varies depending on the country. Thome et al [ 54 ], Ritchie et al [ 53 ], and Elbushra and Ahmed [ 52 ] explained the stronger influence of economic parameters on calorie supply in middle-income countries compared to low-income economies by a lower portion of locally produced staples in consumption.…”
Section: Discussionmentioning
confidence: 99%
“…Muhammad et al [ 160 ] found that the purchase of pricier fruits and milk was particularly sensitive to changes in income and prices. According to Allee et al [ 161 ], an increase in income directly influences an improvement in the food security status of the population, but the strength of this effect varies depending on the country. Thome et al [ 54 ], Ritchie et al [ 53 ], and Elbushra and Ahmed [ 52 ] explained the stronger influence of economic parameters on calorie supply in middle-income countries compared to low-income economies by a lower portion of locally produced staples in consumption.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the availability of cross-country data sets on food and nutrition, substantial progress has been reached in terms of standardization and coverage (Allee et al, 2021). Global information on dietary intake and nutrition (and related health outcomes) has become widely available from UN, FAO, World Health Organisation (WHO) and Global Nutrition Report (GNR).…”
Section: Criteria For An Integrative Food Systems Approachmentioning
confidence: 99%
“…For the cross-country analysis we use the individual components that do justice to the multi-dimensional nature of food systems (Allee et al, 2021) and mirror the conceptualization of multidimensional poverty. However, for the ranking of countries and the comparison of food system transformation with other structural change processes, it is attractive to have an aggregated index at our disposal.…”
Section: Framework For Fsi Developmentmentioning
confidence: 99%
“…Food insecurity is a complex problem at the global, regional, national and sub-national levels with multiple, interconnected causes that manifest as malnutrition, extreme hunger, and starvation (Allee et al, 2018). Food security means that all people have at all times access to sufficient, safe, and nutritious food, while food insecurity can be understood as a continuum, with starvation the most extreme experience (Hendriks, 2015).…”
Section: The Causes Of Acute Food Insecurity and Faminesmentioning
confidence: 99%